2018
DOI: 10.29245/2578-2959/2018/1.1111
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children facing mass trauma: Disasters, war and terrorism

Abstract: Preschool children are exposed to an increasingly wide variety of disasters and terrorist incidents that may have severe effects on their mental health and development. The goal of this paper is to review the research literature regarding the needs of preschoolers in the context of disasters and terrorism with the aim of understanding: a) the consequences of such events for young children and the main moderating variables influencing the eventconsequence association. b) the existing methods for assessment, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Trauma exposure is highly prevalent among both adults and adolescents [1,2], with both groups showing exposurerelated symptoms including withdrawal, sleeping difficulties [3], posttraumatic stress disorder (PTSD) [4], and depression and anxiety symptoms [5], often causing substantial impairment [6]. Several studies [7][8][9] have also shown that adolescents exposed to negative life events (NLEs), i.e., extraordinary experiences with the potential to alter one's social life [10], or potentially traumatic events (PTEs), i.e., experiences which are life-threatening or pose a significant threat to a person's physical or psychological wellbeing [11], at any point during their lives have a markedly increased risk of developing psychopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Trauma exposure is highly prevalent among both adults and adolescents [1,2], with both groups showing exposurerelated symptoms including withdrawal, sleeping difficulties [3], posttraumatic stress disorder (PTSD) [4], and depression and anxiety symptoms [5], often causing substantial impairment [6]. Several studies [7][8][9] have also shown that adolescents exposed to negative life events (NLEs), i.e., extraordinary experiences with the potential to alter one's social life [10], or potentially traumatic events (PTEs), i.e., experiences which are life-threatening or pose a significant threat to a person's physical or psychological wellbeing [11], at any point during their lives have a markedly increased risk of developing psychopathology.…”
Section: Introductionmentioning
confidence: 99%